Apolipoprotein E2 Genotype Is Associated with a 2-Fold Increase in the Incidence of Type 2 Diabetes Mellitus: Results from a Long-Term Observational Study. (7th August 2019) - Santos-Ferreira, Cátia; Baptista, Rui; Oliveira-Santos, Manuel; Costa, Regina; Pereira Moura, José; Gonçalves, Lino
Abstract : Background . The apolipoprotein E (APOE) polymorphisms are associated with cardiovascular (CV) disease, but its interaction with type 2 diabetes mellitus (T2DM) long-term incidence is unknown. We investigated the association between APOE genotype and long-term (i) CV events and (ii) T2DM incidence in a Southern European primary prevention cohort. Methods . We assessed individual APOE genotypes in a total of 436 patients followed at a lipid clinic, with a 15-year median follow-up time. We collected data on major CV events (CV death, myocardial infarction, and stroke) and T2DM development. Results . No differences were found regarding major CV event incidence among the different APOE genotypes. However, after excluding 39 patients with a prior history of T2DM, APOE2 carriers displayed a higher incidence of T2DM during follow-up (42.2%) than APOE3 (27.1%) and APOE4 (28.7%) carriers. The age-, sex-, triglycerides-, and statin usage-adjusted OR for T2DM incidence in APOE2 carriers was 1.8 (95%CI 1.1-2.9, p =0.03), compared with wild-type APOE3. To address the role of statins as a confounder, we analyzed T2DM incidence in statin-treated patients. Statin-treated APOE2 carriers also had a higher T2DM incidence (57.9%), in comparison with APOE3 homozygotes (31.6%) and APOE4 carriers (32.5%). After adjustment for confounding, APOE2 carriers on statins displayed a similar twofold increase in T2DM risk compared to APOE3 homozygotes (OR 2.1, 95%CI 1.1-4.0, p =0.03). Conclusion . Our findings suggest a twofold increase in T2DM incidence in APOE2 carriers. This may prompt for a specific glucose dysmetabolism follow-up that might be tailored on the APOE genotype.